Analysis and Evaluation of Fresnel Zone Antenna Designs - Al-Hindawi, Asaad M. Jassim; Al-Shaikly, Ammar M. (Sulaimani Journal for Pure and Applied Sciences, 2010)
This paper presents an analysis and evaluation of two designs of flat aperture antenna based on Huygen's principle and Fresnel diffraction theory ; therefore, this antenna type is called Fresnel zone plate antenna. The two designs include Soret and Wood types which are different in shape, design procedure and the manufacturing techniques; thus in radiation characteristics. Using the exact solution, the radii of Fresnel zones (rings), directive gain and aperture efficiency of the antenna designs are calculated and the radiation patterns are obtained. It is found that the antenna with odd zones is better in radiation characteristics than the antenna with even zones. It is also determined that the focusing efficiency of Wood antenna design is very good and four times higher than that of Soret type. The obtained results from the two antenna designs are discussed and evaluated.
Keywords: Fresnel zone; aperture antenna; radiation pattern